Design and fabrication of an automatic donut topping machine - Ramizan Nassir, Nurul Athirah (2025)
This dissertation presents a machine designed to revolutionize the donut industry by enhancing the efficiency of the topping application process. The Donut Topping Machine aims to tackle the challenges faced by donut sellers in achieving both uniformity and speed when applying toppings. With this machine, donut shops can quickly and evenly apply toppings such as sprinkles and icing sugar. Its key feature is an automated dispenser that distributes a variety of dry toppings evenly across the surface of each donut, ensuring consistent and efficient application compared to manual methods. This innovation would save time and labor for donut shops while promoting a more uniform and rapid preparation of donuts. Additionally, the machine should have compartments that are easy to clean and maintain, making it suitable for use in a familiar kitchen environment. Market research in the donut industry shows a growing consumer demand for creative and visually appealing toppings, indicating a strong potential market for an efficient solution like this donut topping machine. The primary goal of developing this machine is to simplify the process of applying toppings individually by hand. The anticipated outcome is a machine that effectively distributes toppings as requested by customers.